Cultivating Local Culture Awareness by Using InsideOutside Fishbowl to the Students of Tridinanti University Palembang - Ridha Ilma; Jenny Elvinna Manurung (UICELL, 2017)
Local culture provides a sense of identity for rural communities and residents. This study aimed to describe the improvement of local culture awareness by applying inside-outside fishbowl to the students of Tridinanti University Palembang. Seventeen people of sixth semester students of English study program became the sample of the study. The researchers used a classroom action research as a method of study. This study consisted of two cycles; cycle I and cycle II. Test and observation were used to collect the data. Data calculation showed that there was a significant improvement on students’ local culture awareness, the mean score in cycle I was 67.47 and the mean score in cycle II was 82.35. In other words, the local culture awareness was improved by using inside-outside fishbowl.